Analisis Pembandingan Pola Keanekaragaman Pisang Introduksi Berdasarkan Penanda Fenotipik dengan Penanda RAPD dan Pendugaan Korelasi antara Keduanya terhadap Komposisi Genomiknya - Hanik Rohmah Robi'ah; Sobir Sobir; Memen Surahman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Banana accessions introduced from INIBAP Transit Center (ITC) have been studied their diversity revealed on phenotypic and RAPD markers.  Both of them showed different clustering pattern and not fit to genomic composition. In order to know fitness level of clustering pattern both of them, comparison analysis have done to their similarity coefficient matrix, and followed by partial correlation analysis among phenotypic traits, and genomic composition.  The comparison analysis resulting very poor correlation (r = 0.491). Partially correlation analysis among traits, DNA profile, and Musa genomic composition at 95-99% confidence revealed only OPA-18 line 2 related to accessions possessed pure "A" genome, and they were together associated to green color of petiole margins.  OPD-10 line 3, significantly, associated to accessions with genome dominated "B", but there was no correlation between both of them to any characters. These results suggested that some primers and characters may specifically associated with certain.    Key words:  Comparison analysis, Correlation analysis, Introduction bananas, Musa